2011
DOI: 10.1007/s00296-011-2259-2
|View full text |Cite
|
Sign up to set email alerts
|

The discrepancy between clinical and ultrasonographic remission in rheumatoid arthritis is not related to therapy or autoantibody status

Abstract: To evaluate the clinical remission by means of power Doppler ultrasonographic (PDUS) monitoring in a group of patients with rheumatoid arthritis (RA) in clinical remission (DAS28 < 2.6). The study included 54 patients with RA in therapy with DMARDS, anti-TNF, or no therapy in clinical remission according to ACR criteria and DAS 28 < 2.6 for at least 6 months. All patients had active wrist or hand inflammation in the past. US examination evaluated the presence of active synovitis, power Doppler signal, and syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
1
16
0
3
Order By: Relevance
“…Spinella et al [23] showed that synovial disease might persist despite application of therapy and (good) autoantibody status. The US findings in a TNF-blocker group and those taking other therapies were similar.…”
Section: Discussionmentioning
confidence: 98%
“…Spinella et al [23] showed that synovial disease might persist despite application of therapy and (good) autoantibody status. The US findings in a TNF-blocker group and those taking other therapies were similar.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, B-mode and PD synovitis were detected in 50.7% [20] to 95% of cases [19] and 14.7% [13] to 57.4% of cases, respectively [17]. Only three studies reported the exact number of clinically non swollen joints and the percentage of those with US synovitis among them [9,10,14].…”
Section: Ultrasound Results and Findings Detection Of Infra-clinical mentioning
confidence: 96%
“…The predictive value of B-mode for relapse was only studied in two articles and was not statistically significant [13,19]. Role of ultrasound in assessing remission in rheumatoid arthritis 5 [9,10] 8 Wrist (4 joints) MCP 2-5 Dominant hand Peluso et al, [16] Spinella et al, [17] 12…”
Section: Predictive Value For Relapsementioning
confidence: 96%
See 1 more Smart Citation
“…Не было обнаружено связи между УЗ-динами-кой синовита и характером терапии (монотерапия под-кожным МТ или комбинированная терапия подкожным МТ и ГИБП). Это совпадает с данными других авторов, которые не отметили различий в динамике ультразвуко-вой картины синовита у пациентов, получавших ингиби-торы ФНОα или монотерапию МТ [43,44]. Это имеет принципиальное значение, поскольку персистенция «субклинического» воспаления у больных РА, находя-щихся в «клинической» ремиссии (или имеющих низкую активность заболевания), ведет к нарастанию деструктив-ных изменений в суставах и функциональной недостаточ-ности [10,45] и ассоциируется с обострением заболева-ния после отмены терапии [46].…”
Section: таблицаunclassified